Hak Pendapatan Pekerja Perempuan dalam Al-Qur’an - N. Noorchasanah (UIN Sunan Gunung Djati, 2020)
The Qur'an teaches about balance relationship between men and women in the scope of social life. In reality, there are a lot of scholars and interpretator have the point of view that women should limit themselves to be active in the public area’s. So there are the issues related to the protection of the income rights of women workers themselves. Wahbah Zuhaili and Quraish Shihab itself was a figure of nowadays interpretator who often discuss gender equality. The model used in this interpretation is a descriptive analysis, which revealed the interpretation Wahbah Zuhaili and Quraish Shihab is based on the issues related to interpretation books Al-Misbah and Al-Munir. The thematic interpretation methods used in assessing the verses associated with it, particularly on gender. Wahbah Zuhaili and Quraish Shihab explain that women have equal status with men because women have their own rights. so it is fitting female workers have the same rights as male workers, both in terms of income, protection, opportunities of employment and gain comfort within the scope of its work. And this was in accordance with the rules possessed by Islam itself, where men and women both are equal and equally rewarded in accordance with what has been cultivated by the individual. Wahbah Zuhaili and Quraish Shihab also prohibit discrimination on the matter. So that the results of the analysis are expected to be implemented in the making of policies relating to the income rights of women workers themselves.